PENGEMBANGAN MULTIMEDIA INTERAKTIF DENGAN MENGGUNAKAN SOFTWARE ADOBE DIRECTOR 11 PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI KELAS X SMAN 2 BATUSANGKAR - Ekstrada, Erik (El -Hekam, 2020)
This study begins with the findings at SMAN 2 Batusangkar on PAI and Budi Pekerti class X learning that teachers only use the packet book in the learning process in the classroom. The package book was less able to attract attentionand increase students' understanding of learning materials. The aims of study to develop a valid and practical interactive multimedia in order to overcome these problems. The type of research that the authors use is research and development. Instruments used are observation guides, interview guides and questionnaires. Data collection techniques that the author uses are observation, interviews and questionnaires. Data analysis technique consists of two ways, qualitative data analysis techniques by Miles and Huberman and quantitative descriptive data analysis techniques. Interactive multimedia has been feasible to be used as a learning PAI and Budi Pekerti. This is taken in accordance with the level of validity and practicality that has been analyzed in this study.